1-(2,4-Dinitrophenyl)-2-[(E)-(3,4,5-trimethoxybenzylidene)] hydrazine - Chantrapromma, Suchada; Ruanwas, Pumsak; Boonnak, Nawong; Chidan Kumar, C. S.; Hoong, Kun Fun (International Union of Crystallography, 2014)
Molecules of the title compound, C16H16N4O7, are not planar with a dihedral angle of 5.50 (11) between the substituted benzene rings. The two meta-methoxy groups of the 3,4,5- trimethoxybenzene moiety lie in the plane of the attached ring [Cmethyl–O–C–C torsion angles 0.1 (4) and 3.7 (3)] while the para-methoxy substituent lies out of the plane [Cmethyl— O—C—C, 86.0 (3)]. An intramolecular N—H O hydrogen bond involving the 2-nitro substituent generates an S(6) ring motif. In the crystal structure, molecules are linked by weak C—H O interactions into screw chains, that are arranged into a sheet parallel to the bc plane. These sheets are connected by – stacking interactions between the nitro and methoxy substituted aromatic rings with a centroid– centroid separation of 3.9420 (13) A ° . C—H contacts further stabilize the two-dimensional network.